Perioptic Cerebrospinal Fluid Dynamics in Idiopathic Intracranial Hypertension - Pircher, Achmed; Montali, Margherita; Pircher, Joachim; Berberat, Jatta; Remonda, Luca; Killer, Hanspeter E. (Frontiers in Neurology, 2018)
Purpose: To examine the cerebrospinal fluid (CSF) dynamics along the entire optic nerve in patients with idiopathic intracranial hypertension (IIH) and papilledema by computed tomographic (CT) cisternography. Methods: Retrospective analysis of CT cisternographies in 16 patients with a history of IIH and papilledema (14 females and 2 males, mean age: 49±16 years). Contrast loaded CSF (CLCSF) was measured in Hounsfield Units (HU) at three defined regions of interest (ROI) along the optic nerve (orbital optic nerve portion: bulbar and mid-orbital segment, intracranial optic nerve portion) and additionally in the basal cistern. The density measurements in ROI 1, ROI 2 and ROI 3 consist of measurements of the optic nerve complex: optic nerve sheath, CLCSF filled SAS and optic nerve tissue. As controls served a group of patients (mean age: 60±19 years) without elevated intracranial pressure and without papilledema. Results: In IIH patients the mean CLCSF density in the bulbar segment measured 65±53 HU on the right and 63±35 HU on the left side, in the mid-orbital segment 68±37 HU right and 60±21 HU left. In the intracranial optic nerve portion 303±137 HU right and 323±169 HU left and in the basal cistern 623±188 HU. Within the optic nerve the difference of CLCSF density showed a highly statistical difference (p<0.001) between the intracranial optic nerve portion and the mid-orbital segment. CLCSF density was statistically significantly (p<0.001) reduced in both intraorbital optic nerve segments in patients with IIH compared to controls. Conclusions: The current study demonstrates reduced CLCSF density within the orbital optic nerve segments in patients with IIH and papilledema compared to 12 controls without elevated intracranial pressure and without papilledema. Impaired CSF dynamics could be involved in the pathophysiology of optic nerve damage in PE in IIH. Key words: Idiopathic intracranial hypertension, cerebrospinal fluid, optic nerve, optic canal, optic nerve sheath compartment